THEORITICAL ASPECTS OF COMPARATIVE LINGUISTICS (World Bulletin of Social Sciences, 2023)
Since our state gained its independence, it has paid attention to every sector of society. More and more reforms have been implemented, with education receiving the majority of the focus. "The Law of the Republic of Uzbekistan on Education" and "The Law of the Republic of Uzbekistan on the National Program of Personnel Training System" were both adopted in the early years of independence. Every change undertaken, regardless of field, has the individual as its primary goal. Islam Abduganiyevich Karimov, our first president, wanted the Uzbek nation to be less advanced than other nations. Today, however, thanks to a calm atmosphere, freedom, and a number of changes, scientists may explore the field and elevate our motherland to the top.